KEMAMPUAN ANALISIS DATA PENELITIAN MAHASISWA FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM TASIKMALAYA BERBANTUAN SOFTWARE STATISTICAL PRODUCT AND SERVICE SOLUTIONS (SPSS) - Rohman, Taufik (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Data analysis is the process of processing data with the aim of finding useful information that can be used as a basis for making decisions to solve a problem. This analysis process includes activities of grouping data based on its characteristics, performing data cleaning, transforming data, creating data models to find important information from the data. Do not forget that data that has gone through this process must be presented in an attractive and easy-to-understand form by others in the form of output tables, graphs or plots. The ability to analyze data is one of the skills that must be possessed by students of the Tarbiyah Faculty of IAI Tasikmalaya. Students are facilitated by learning data analysis with the help of Statistical Product and Service Solutions (SPSS) software in statistics courses. This study aims to analyze students' abilities in conducting SPSS-assisted research data analysis. This research was conducted on Tarbiyah Faculty IAI Tasikmalaya students who contracted a statistics course. The sample is determined by purposive sampling. Data was collected during January 2023. Student ability data was collected through assignment results. The level of ability is determined based on the degree of mastery with a range of 0 – 100 and grades A – E. This value is interpreted into 5 categories. Other data collected is student responses to their learning experiences. Data analysis used descriptive statistics to determine the degree of mastery, average and proportion. The findings from this study were that students were able to perform SPSS-assisted research data analysis in the good category. These findings indicate that students are ready to complete their thesis from the aspect of data analysis.